Eksplorasi dan Analisis Tumbuhan Hiperakumulator Ni di Ekosistem Hutan Jangkauan Nikel di Sulawesi Tenggara, Indonesia - Faisal; Nina Ratna Djuita; Hamim (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia, as the world's largest nickel producer, has vast ultramafic areas that have the potential to become habitats for nickel hyperaccumulator plants (Ni). This study aimed to explore and analyze nickel hyperaccumulator plants in the mining area of CV. Unaaha Bakti Persada, North Konawe Regency, Southeast Sulawesi, Indonesia. The research was conducted from June to November 2023 using the exploration method at three observation stations, each consisting of three plots. The research stages carried out include exploration, plant collection and identification, and analysis of Ni content in soil as well as plant tissue using Atomic Absorption Spectrophotometry (AAS). A total of 32 plant species were found, which was dominated by Pteridium aquilinum ferns at Stations I and III and Scleria lithosperma grasses at Station II. The Ni content of the soil was very high (5,458.32–5,938.41 mg/kg) and far above the normal threshold. Several species showed high Ni accumulation capacity, with the most of six were Sarcotheca celebica, Knema metanensis, Pluchea carolinensis, Gymnostoma sumatrana, and Justicia gendarussa. The post mining sites were categorized as marginal due to heavy metal toxicity (Ni, Co, Cr), and therefore, only tolerant plants can survive. Sarcotheca celebica had the highest BCF value (0.1421) and was classified as a moderate accumulator. All the six species has the potential to be used for phytoremediation, phytomining and reclamation of post mining areas in Southeast Sulawesi.